The war in Europe: Economic costs of the Ukrainian conflict - Julia Bluszcz; Marica Valente (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
With more than ten thousand casualties, the 2014 Ukrainian war between pro-Russian separatists and the government in the Donbass region, Ukraine's productive core, has taken a severe toll on the country. Using cross-country panel data over the period 1995-2017, this paper quantifies the short-term causal effects of the Donbass war on Ukraine's GDP. Results from the counterfactual estimation by the synthetic control method show that Ukraine's per capita GDP foregone due to the war amounts to 15.1% on average for 2013-2017. Separate analysis for the affected provinces of Donetsk and Luhansk indicate an average causal effect of 43% for 2013-2016. Confoundedness checks obtained by iteratively estimating synthetic controls on the pre-war period to account for previous Ukrainian-Russian disputes show robustness of the results.
Keywords: D74; P16; C21; G14; 330; conflict; economic costs; Donbass; synthetic control